Quatum chemistry - McQuarrie, Donald A. (New Delhi: Viva Books, 2003)
The book has been selectively updated throughout, with perhaps the most significant revision being the incorporation of computer power. The new edition covers quantum chemistry programs such as Gaussian and WebMo, and encourages the use of programs such as MathCad and Mathematica to perform calculations with hitherto unheard of ease. The new edition has also included a series of short math "refresher" inserts spaced intermittently throughout the book to help students focus on the physical principles being explained rather than struggling with the underlying mathematics. The book assumes a prerequisite of one year of calculus with no required knowledge of differential equations.
Index 512-517p.
Keywords: Molecular spectroscopy; Molecules; Quantum chemistry; Chemistry